2000
DOI: 10.1074/jbc.m007849200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Immunoreceptor Tyrosine-based Activation Motif-containing Molecule, STAM2, by Mass Spectrometry and Its Involvement in Growth Factor and Cytokine Receptor Signaling Pathways

Abstract: In an effort to clone novel tyrosine-phosphorylated substrates of the epidermal growth factor receptor, we have initiated an approach coupling affinity purification using anti-phosphotyrosine antibodies to mass spectrometry-based identification. Here, we report the identification of a signaling molecule containing a Src homology 3 domain as well as an immunoreceptor tyrosine-based activation motif (ITAM). This molecule is 55% identical to a previously isolated molecule designated signal transducing adaptor mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 29 publications
2
76
0
Order By: Relevance
“…These two kinases are involved in many growth factor-and cytokine-dependent signaling pathways, and their essential roles have been demonstrated by gene targeting studies (47,48). Recent intensive analyses of protein expression patterns have revealed that many tyrosine-phosphorylated substrates are involved in growth factor-dependent signaling, and some of these may require Jaks for their phosphorylation (49,50). Therefore, we speculate that both Jak1 and Jak2 are involved in Stat1-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…These two kinases are involved in many growth factor-and cytokine-dependent signaling pathways, and their essential roles have been demonstrated by gene targeting studies (47,48). Recent intensive analyses of protein expression patterns have revealed that many tyrosine-phosphorylated substrates are involved in growth factor-dependent signaling, and some of these may require Jaks for their phosphorylation (49,50). Therefore, we speculate that both Jak1 and Jak2 are involved in Stat1-independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Two human Stam homologs have been described (Takeshita et al 1996;Endo et al 2000;Pandey et al 2000;Takata et al 2000). Stam proteins are constitutive binding partners of the Hepatocyte growth factor-regulated substrate (Hrs) (Asao et al 1997;Takata et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Single phosphoproteins can be purified from a cell lysate by immunoprecipitation using antibodies [23]. After immunoprecipitation, the sample can be separated by SDS-PAGE and the correct protein band of interest is excised and further analyzed by MS. Antibodies against phosphorylated serine, threonine, and tyrosine residues can be used for the overall enrichment of phosphoproteins from a complex sample, though, this method is limited by the specificity of the antibodies [28,29]. Tyrosine phosphorylation, in particular, is of very low abundance.…”
Section: Immunoaffinity Chromatographymentioning
confidence: 99%